Enhancing composite Digital Documents Using XML-based Standoff Markup - Thomas, Peter L.; Brailsford, David F. (ACM Press, 2005)
Document representations can rapidly become unwieldy if they try to encapsulate all possible document properties, ranging from abstract structure to detailed rendering and layout. We present a composite document approach wherein an XMLbased document representation is linked via a shadow tree of bi-directional pointers to a PDF representation of the same document. Using a two-window viewer any material selected in the PDF can be related back to the corresponding material in the XML, and vice versa. In this way the treatment of specialist material such as mathematics, music or chemistry (e.g. via read aloud or play aloud ) can be activated via standard tools working within the XML representation, rather than requiring that application-specific structures be embedded in the PDF itself. The problems of textual recognition and tree pattern matching between the two representations are discussed in detail. Comparisons are drawn between our use of a shadow tree of pointers to map between document representations and the use of a code-replacement shadow tree in technologies such as XBL.